Developing the Sexual Education E-Comic “Serat Widya Pramana” as a Prevention of Early Marriage - Dewantari, Anindhea Putri Kusuma; Rizkinalbarokah, Arina; Veronica, Auzriella Cherrya Dian; Sitepu, Hanindya Anya; Sadida, Winandriya Hanun; Andayani, Tri Rejeki (Indigenous: Jurnal Ilmiah Psikologi, 2025)
Although various sexual education media have been developed, the number of marriage dispensation applications continues to show a worrying upward trend. This indicates that the existing educational efforts have not been effective in preventing early marriage. Therefore, an innovative approach is needed to produce sexual education media that is more effective and comprehensive. This study aims to develop an alternative medium of child marriage prevention in Surakarta City in the form of Serat Widya Pramana-Based Sexual Education E-Comic. The research employed the Research and Development method, covering three out of five stages of the ADDIE model (Analysis, Design, Development). The e-comic development was evaluated for its content, linguistic and media feasibility by experts and potential users. Additionally, pilot testing was conducted on a small-scale research subject using a Quasi-Experimental One-Group Pretest-Posttest design. The e-comic received a score of 68 (good) from the healthy reproduction material expert, 80 (good) from the literature expert, 96 (excellent) from the language experts, 90 (excellent) from the media experts, and 69.3 (good) from prospective users. Subsequently, pilot testing was carried out on 10 (4 females and 6 males) adolescents from SMK "X" Surakarta. Data analysis using the Paired Sample T-Test showed a significant increase in sexual knowledge (p=0.000, p<0.05) and a significant decrease in adolescents' intention toward early marriage (p=0.008, p<0.05). Therefore, the Sexual Education E-Comic Serat Widya Pramana is deemed suitable as an alternative medium for preventing early marriage in Surakarta City.